Dual microglia effects on blood brain barrier permeability induced by systemic inflammation - Koichiro Haruwaka (Nature Portfolio, 2019)
Although it is known that microglia respond to injury and systemic disease in the brain, it is unclear if they modulate blood–brain barrier (BBB) integrity, which is critical for regulating neuroinflammatory responses. Here authors demonstrate that microglia respond to inflammation by migrating towards and accumulating around cerebral vessels, where they initially maintain BBB integrity via expression of the tight-junction protein Claudin-5 before switching, during sustained inflammation, to phagocytically remove astrocytic end-feet resulting in impaired BBB function